Efficacy and Safety of CAR-Modified T Cell Therapy in Patients with Relapsed or Refractory Multiple Myeloma: A Meta-Analysis of Prospective Clinical Trials - Xiang, Xinrong; He, Qiao; Ou, Yang; Wang, Wen; Wu, Yu (Frontiers in Pharmacology, 2020)
Background: In the past few years, chimeric antigen receptor (CAR)-modified T cell therapy for B cell leukemia and lymphoma has shown high clinical efficacy. However, no systematic review is available on the efficacy and safety of CAR-T cell therapy in refractory/relapsed multiple myeloma (RRMM). The purpose of this study was to fill this literature gap. Methods: Eligible studies were searched in PUBMED, EMBASE, the Cochrane Central Register of Controlled Trials (CENTRAL), CNKI, and WanFang from data inception to Dec, 2019. For efficacy assessment, the overall response rate (ORR), minimal residual disease (MRD) negativity rate, strict complete response (sCR), complete response (CR), very good partial response (VGPR), and partial response (PR) were calculated. The incidence of any grade cytokine release syndrome (CRS) and grade ≥3 adverse events (AEs) were calculated for safety analysis. We pooled the effect estimates using an inverse variance method. Results: Overall, 27 studies involving 497 patients were included in this meta-analysis. The pooled ORR and MRD negativity rate were 89% (95%Cl: 83%−94%) and 81% (95%Cl: 67%−91%), respectively. The pooled sCR, CR, VGPR, and PR were 14% (95%Cl: 5%-27%), 13% (95%Cl: 4%-26%), 23% (95%Cl: 14%-33%), and 15% (95%Cl: 10%-21%), respectively. Subgroup analyses of ORR by age, proportion of previous autologous stem cell transplantation (ASCT), and target selection of CAR T cells revealed that age≤55 years (≤55 years vs >55years, p=0.0081), prior ASCT≤70% (≤70% vs >70%, p=0.035), and bispecific CAR-T cells (dual B cell maturation antigen (BCMA)/ BCMA+CD19 vs specific BCMA, p=0.0329) associated with higher ORR in patients. Subgroup analyses of remission depth by target selection suggested that more patients achieved a better response than VGPR with dual BCMA/BCMA+CD19 CAR-T cells compared to specific BCMA targeting(p=0.0061). For safety analysis, the pooled incidences of any grade and grade ≥3 CRS were 76% (95%CL: 63%−87%) and 11% (95%CL: 6%−17%), respectively. The most common grade ≥3 AEs were hematologic toxic effects. Conclusions: In heavily treated patients, CAR-T therapy associates with promising outcomes and tolerable AEs and CRS in RRMM. However, additional information about the durability of CAR-T cell therapy, as well as further randomized controlled trials, are needed.